PEMAHAMAN KHALAYAK BONE TERHADAP PENGGUNAAN TAGAR INSTAGRAM #DIRUMAHAJA PADA MASA COVID-19 - Qudratullah Qudratullah; Febriyanti Nurgahayu; Nur Afiq Nur (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
This study aims to find out the understanding of Bone's audience towards the use of Instagram hashtags #dirumahaja during the Covid-19 period. This study uses the phenomenological method because it is considered suitable for the object of study whose study is the use of #dirumahaja in line with the phenomenon of the Covid-19 outbreak. As for the phenomenological method, we are referring to, it is a description of a person's life experience. It is necessary to know how a person expresses his experience through the consciousness that occurs in a person or individual. audiences have used Instagram as a medium to get information and entertainment media. The results of this study show that bone audiences have also understood the use of hashtag #dirumahaja in depth is characterized by being able to translate, namely giving meaning to the hashtag, then the audience has also been able to interpret the use of these hashtags as a preventive effort and finally audience at Bone has also reached the exploratory stage, namely being able to connect or bring the meaning of this understanding to other things, like gaping himself is a participant of this Covid-19 plague.